EFEKTIVITAS KOMBINASI JUS KACANG HIJAU DAN KURMA TERHADAP KADAR HB PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS PANIPAHAN KABUPATEN ROKAN HILIR - Dessika, Dessika; Ruspita, Rika; Sri Rahayu, Ari Oktora; Fitria, Nurhidaya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Until now, there are still many pregnant women who do not comply with taking Fe tablets, one of the reasons is the side effects of the Fe tablets, therefore pregnant women are susceptible to anemia. The aim of the research was to determine the effectiveness of a combination of green bean juice and dates on HB levels in pregnant women. This type of research is quantitative and pre-experimental design, one group design with pretest-posttest. This research was conducted at the Panipahan Community Health Center, Rokan Hilir Regency. The population is pregnant women and a sample of 12 people, with. total sampling. The research instruments were observation sheets and SOPs. Data analysis uses univariate and bivariate. Univariate results showed that the majority of pregnant women's Hb levels at the Panipahan Community Health Center, Rokan Hilir Regency were in the mild anemia category, namely 100% before being given a combination of green bean and date juice, and after being given it, pregnant women were not anemic, namely 91.7%. Bivariate results showed that giving a combination of green bean juice and dates was effective in increasing hemoglobin levels in pregnant women at the Panipahan Community Health Center, Rokan Hilir Regency, with a p-value of 0.000 < 0.05. Keywords: Green Beans, Dates, Hb Levels, Hemoglobin, Pregnant Mother.